DAMPAK TERPAPAR TOLUENA TERHADAP KADAR ASAM HIPURAT URIN PADA PEKERJA PENGECATAN OVEN OTOMOTIF - Adi Rahmat (Jurnal Penelitian Kesmasy, 2019)
Toluene can be detected through urine and blood, in toluene urine can be examined through hypuric acid. Examination of hypuric acid in urine is one type of biological monitoring that is important in initiating and measuring toluene exposure in the workforce. This research was conducted at two Acapella workshops for automotive oven painting with a sample of 12 workers. The results showed that attention to occupational health and safety programs, especially efforts to prevent the occurrence of side effects due to exposure to toluene vapor was still low, the average level of urine hypuric acid in the workers in the morning was still at the normal threshold (1.68 g/g) , and increases in the afternoon (5.03 g/g) even though there are some workers who have levels that are far above the normal threshold value, Variables of age and years of service have a role in determining the level of hypuric acid, where the working period has a greater role than the age variable.